Return to health and performance following COVID-19 infection - McCluskey, P.; Benson, B.; Leclerc, S.; Richards, D.; Wilkinson, M.; Marshall, A.; McCormack, R.; Van Neutegem, A. (2020)
This document provides a guideline for National Sport Organizations (NSOs), National Development (i.e., NextGen), and Provincial Sport Organizations (PSOs) teams regarding return to health and performance following severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2, or COVID-19) infection in the Canadian Olympic and Paralympic Sport Institute (COPSI) Network. It is applicable to adult-aged, high-performance athletes who have mild to moderate illness. Management of athletes still symptomatic with severe illness requiring hospital admission is beyond the scope of this guideline. The COPSI Network guideline will be frequently reviewed and updated with any new medical and scientific advances, and/or national health authority regulatory changes, and/or with any learned experiences through implementation. Healthcare professionals directly involved with high-performance athlete care should remain up-to-date with COVID-19 related information and must adhere to their national / provincial / regional public health authority recommendations to reduce any unnecessary risks and help reduce the spread of COVID-19. Feasibility, cost considerations and burdening of local health care systems should all be considered for various levels of the recommended investigations for low-risk individuals. Given the unknown potential for adverse and/or long-lasting effects of COVID-19-related complications† in high-performance athletes, consideration for further investigation and consultation by a (sports) cardiologist and/or respirologist must be considered before return to training/sport, particularly if the athlete has pre-existing comorbidities that may increase the risk of serious illness such as heart disease (e.g., heart failure, coronary artery disease, cardiomyopathies), high blood pressure, diabetes, chronic lung disease, moderate to severe asthma, chronic kidney disease, sickle cell disease, thalassemia, liver disease, cystic fibrosis, immunocompromised status or impaired recovery of exercise capacity12. Furthermore, consideration of mental health support for the COVID-19 infected athlete is of critical importance.